PELATIHAN HOUSEKEEPING DALAM RANGKA PENINGKATAN PELAYANAN HOMESTAY DI DESA CISAAT KABUPATEN SUBANG JAWA BARAT - Mulyati; Nurlaila A.M, Mashabi; Prastitilaras Nugraheni (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract Tourist village Cisaat Subang is one of the villages tourisms made especially education tourism is one of the sectors of the people come from the driving force of the economic. This village located in Subang district, West Java and the age of this village is relatively new in the context of rural tourism, therefore development is needed, especially in the field of human resources in the tourism sector, one of which is the homestay manager which is expected to be able to increase the number of tourist visits which will certainly have a direct impact for the welfare of the citizens of Cisaat Village. One of the efforts needed is the need for training, namely housekeeping training. The purpose of Community Service Integrated Community Service Program is to increase community resources by improving the services of homestay managers according to the ASEAN Homestay Standard with local wisdom in the form of soft & hard skills and increasing public understanding and awareness about tourism. The form of this activity is briefing in the form of lectures and discussions by using the housekeeping module which can be used as a guide in structuring homestays and direct practice in the form of structuring homestays. This activity was carried out in September 2021. Based on the results measured by pre-test and post-test, the training provided can be concluded that there is an increase in the ability of participants in knowledge of homestay arrangement. The community feels the benefits of this activity and hopes that this activity will continue in the future. Abstrak Desa wisata Cisaat Subang adalah salah satu desa yang menjadikan wisata khususnya wisata edukasi sebagai salah satu sektor penggerak ekonomi masyarakatnya. Desa ini berada di kabupaten Subang Jawa Barat dan secara usia desa ini tergolong baru dalam konteks wisata pedesaan, oleh karena itu diperlukan pengembangan khususnya di bidang sumber daya manusia bidang kepariwisataan salah satunya pengelola homestay yang diharapkan mampu meningkatkan jumlah kunjungan wisatawan yang tentunya akan berdampak secara langsung bagi kesejahteraan warga Desa Cisaat. Salah satu upaya dibutuhkan adalah diperlukannya pelatihan yaitu pelatihan housekeeping. Tujuan dari Pengabdian Pada Masyarakat Terintegrasi KKN adalah untuk meningkatkan sumber daya masyarakat dengan peningkatan pelayanan para pengelola homestay sesuai ASEAN Homestay Standard dengan kearifan lokal berupa soft & hard skill dan peningkatan pemahaman serta kesadaran masyarakat mengenai kepariwistaan.Bentuk kegiatan ini adalah Pembekalan dalam bentuk ceramah dan diskusi dengan menggunakan modul housekeeping yang dapat dijadikan pedoman dalam penataan homestay dan praktek langsung berupa penataan homestay. Kegiatan ini dilaksanakan pada Bulan September 2021. Berdasarkan hasil yang diukur dengan pre-test dan post-test,pelatihan yang diberikan dapat disimpulkan bahwa terjadi peningkatan kemampuan peserta dalam pengetahuan penataan homestay. Masyarakat merasakan manfaat dari kegiatan ini dan mengharapkan kegiatan ini masih akan terus dilanjutkan di masa mendatang.